Omission errors in medical prescriptions dispensed in a Public Health Center of Iztapalapa in Mexico City in 2021 - Hernández-Retana, Kenya; Heyerdahl-Viau, Ivo; Pérez-Sánchez, Roberto; Gómez-Sánchez, Armando Carlos; García-Casas, Mireya; Martínez-Núñez, Juan Manuel (Medicina Clínica y Social, 2024)
Introduction: Prescription errors cover a wide range of errors that can range from an incorrect selection of the medication to the lack of important information in the medical prescription, the latter called omission errors, which can affect the patient's health. However, in Mexico there are no reports on omission errors in first-level care centers, which are the institutions that address the majority of the population's health problems. Objective: To determine the prevalence of omission errors identified in medical prescriptions issued in a first-level health center in Mexico City in 2021. Methods: This is an observational, cross-sectional and retrospective study. Eleven types of omission errors present in medical prescriptions were analyzed according to current Mexican regulations. The prevalence of each type of error was estimated and the rate of omission errors was calculated. Results: A total of 5822 medical prescriptions were analyzed and 3424 omission errors were found. The error rate was 1.08 errors per prescription. The most frequently found errors were the omission of the diagnosis/medication relationship (38.91%), the pharmaceutical form (30.54%) and the concentration (12.11%). Discussion: A high prevalence of omission errors was found in medical prescriptions at the health center that hosted the study in 2021. It is necessary to implement support systems for health professionals with a view to reducing prescription errors.
Keywords: medical errors; Mexico; prescriptions